THE INFLUENCE OF DIVIDEND PAYOUT, ASSET INTENSITY, AND DEBT INTENSITY ON COST STICKINESS - Hempry Putuhena; M. Rifkhi Fauzan S.; Zalni (CV. Adiba Aisha Amira, 2026)
Cost stickiness is an important concern in management accounting studies because it indicates asymmetric costs. Operating costs tend to rise when sales increase but not when sales decline. This condition has significant implications for business sustainability. The purpose of this study is to investigate the impact of dividend payout, asset intensity, and debt intensity on cost stickiness in companies listed in LQ45 from 2019 to 2022). This study tests the drivers between independent and dependent variables using a quantitative approach. The study's secondary data originates from financial filings that have been made public. According to the study findings, cost stickiness is influenced by asset intensity and dividend payout to a partially extent, but not by the debt intensity variable. Since cost behavior through cost stickiness can maximize the achievement of company goals and identify the right use of resources, it is important for the company to manage it appropriately. Monitoring and controlling dividend payout, asset intensity, and debt intensity are necessary to ensure that they maximize the potential to boost sales.